Preparation method of Fenton-like catalytic material for selectively removing phenolic pollutants, Fenton-like catalytic material and application of Fenton-like catalytic material
By preparing a sheet-like Ce@Cu(OH)2-IE catalytic material, the problems of low efficiency and high CO2 emissions of existing catalysts were solved, achieving highly efficient and selective oxidation and high TOC removal, which is suitable for the treatment of phenolic pollutants in complex water bodies.
Patent Information
- Application Number
- CN202410945106.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-01-10
AI Technical Summary
Existing persulfate-activated catalysts have low oxidant utilization efficiency, low TOC removal efficiency, and high CO2 emissions, making it difficult to meet the treatment needs of high water quality standards and complex water body backgrounds.
Copper hydroxide nanoparticles were prepared using light MgO as raw material, and cerium was doped through hydrothermal reaction to form Ce@Cu(OH)2 intermediate. Finally, the intermediate was obtained by high-temperature calcination in air to obtain a plate-like Fenton-like catalyst CC-I E. The catalyst utilizes the oxidative polymerization mechanism to efficiently activate PMS to generate singlet oxygen, thereby achieving selective oxidation and high TOC removal.
It achieves high electron utilization, selective oxidation and non-radical degradation, has a high TOC removal rate, can stably remove phenolic pollutants in complex water environments, and recover organic carbon, reducing CO2 emissions.
Smart Images

Figure CN119281337A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water treatment, and in particular relates to a preparation method of a Fenton-like catalytic material for selectively removing phenol pollutants, a Fenton-like catalytic material and an application thereof. Background Art
[0002] Advanced oxidation process (AOP), especially peroxymonosulfate (PMS) activation, is the most advanced water purification wastewater treatment technology, which relies on highly active free radicals (·OH and SO4· - ) or other non-radical pathways to remove stubborn organic pollutants. Among the alternative non-radical pathways, singlet oxidation has attracted much attention due to its inherent advantages such as long lifetime, wide pH tolerance, strong electrophilicity and selectivity. Typically, singlet oxygen is formed via self-decay, nucleophilic addition and catalytic activation of persulfates such as PMS. Singlet oxidation in PMS AOPs exhibits high selectivity towards electron-rich organic matter or bacteria and maintains excellent efficiency in complex environmental disturbances.
[0003] To achieve sustainable wastewater treatment with an emphasis on energy and resource recovery, remediation technologies based on the synergistic effects of adsorption and oxidative polymerization offer new strategies that have the potential to effectively transform refractory organic matter into value-added products rather than oxidative degradation to useless intermediates or complete mineralization to CO2 and H2O.
[0004] The study found that nanocatalysts can interact with persulfate and activate pollutants by reducing their reduction potential, thereby triggering the non-decomposition oxidation transfer of pollutants from the bulk solution to the surface of the nanocatalyst. During the reaction, the nanocatalyst has the functions of surface activation, stability and accumulation. By making full use of this characteristic, effective treatment of wastewater can be achieved, and effective removal of TOC in water can be achieved with less oxidant consumption, but this requires a slightly alkaline environment to obtain satisfactory results, and strict pH control is required.
[0005] In order to solve the above problems, active metals are usually loaded on stable metal or non-metal matrix materials to prepare persulfate activation catalysts. The relevant patents disclosed are as follows:
[0006] A method for activating Fe(III)-driven Fenton-like reaction system using PDA@MoN and its application (Patent Publication No.: CN 117299180A). The patent ultrasonically disperses MXene in ultrapure water, adds dopamine, stirs thoroughly to polymerize dopamine on the surface of MXene, washes and freeze-dries in vacuum after the reaction, and finally calcines in an ammonia atmosphere to obtain PDA@MoN. This material is used as a heterogeneous Fenton-like catalyst to solve the problems of the small pH application range of the existing homogeneous Fenton system, low oxidant utilization efficiency, and iron mud generation during the reaction. However, the preparation conditions of this scheme require vacuum drying and calcination in ammonia, the reaction conditions are demanding, the production risk is high, and the cost of the raw material MXene is high, which is not conducive to large-scale promotion and manufacturing.
[0007] A method for preparing a catalyst for removing ciprofloxacin by an efficient Fenton-like method (CN 114870845 B). The patent discloses a method for preparing a novel catalyst for removing ciprofloxacin by an efficient Fenton-like method. The target material can be obtained by adding ferric nitrate nonahydrate and cobalt nitrate hexahydrate, freeze-drying at -40°C and pyrolyzing at high temperature under a nitrogen atmosphere. The catalyst provided by the invention is non-toxic and environmentally friendly. It is prepared by simple mixing and cross-linking, and doped with magnetic microspheres to quickly degrade antibiotic pollutants. By adding 10 mg of catalyst and 0.1 mmol potassium persulfate, 100 mL, 20 mg / L ciprofloxacin solution can be degraded by 90% within 10 minutes. However, the patent does not mention the ideal TOC removal rate and complex water quality background, which is not conducive to high-standard effluent TOC requirements and complex water matrix.
[0008] A Fenton-like catalyst of clustered manganese dioxide loaded with iron and its preparation method (patent publication number CN202110694536.8). Divalent manganese salt and oxidant are mixed evenly in a certain proportion, and a hydrothermal reaction is carried out. After the reaction is completed, the mixture is cooled, washed and dried, and ground to obtain clustered MnO2; the prepared MnO2 is then subjected to a hydrothermal reaction with a certain concentration of trivalent iron solution and urea solution. A two-step hydrothermal method is used to prepare highly dispersed clustered manganese dioxide loaded with iron. The materials used have high stability and are non-toxic and harmless, and will not cause waste of resources and the formation of additional pollution. The preparation process is simple and efficient; the obtained material maintains a high specific surface area while presenting a relatively large particle state, which is convenient for recycling and reuse; the obtained Fenton-like catalyst has a high TOC removal rate and organic pollutant removal rate. However, the TOC in this scheme is converted into carbon dioxide after removal, which is not conducive to the achievement of the dual carbon goals.
[0009] Therefore, there is an urgent need to develop heterogeneous Fenton-like catalytic materials with high economic benefits, strong anti-interference ability, high oxidant activation efficiency, high TOC removal rate, and the ability to maximize the reduction of CO2 emissions. Summary of the invention
[0010] In order to solve the problems of low oxidant utilization efficiency, low TOC removal efficiency and large CO2 emission of existing persulfate activated catalysts, the present invention provides a method for preparing a Fenton-like catalytic material for selectively removing phenol pollutants. The Fenton-like catalytic material prepared by the preparation method can efficiently activate PMS to generate singlet oxygen, can utilize an oxidative polymerization mechanism to stably remove organic phenol pollutants in water, and has the advantages of high electron utilization, selective oxidation, non-radical pathway degradation and high TOC removal rate.
[0011] The present invention also provides a Fenton-like catalytic material for selectively removing phenol pollutants and application thereof.
[0012] The present invention is achieved through the following technical solutions:
[0013] The present invention provides a method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants, the preparation method comprising:
[0014] Light MgO is added to a copper nitrate solution, stirred and reacted for a certain period of time, and the resulting precipitate is filtered, washed and dried to obtain copper hydroxide nanoparticles;
[0015] The copper hydroxide nanoparticles are dispersed in a cerium nitrate solution, followed by a hydrothermal reaction, and the resulting precipitate is filtered, washed, and dried to obtain a Ce@Cu(OH)2-IE intermediate;
[0016] The Ce@Cu(OH)2-IE intermediate is calcined to obtain the Fenton-like catalytic material CC-IE.
[0017] Furthermore, the light MgO is added to the copper nitrate solution, stirred for a certain period of time, and the obtained precipitate is filtered, washed and dried to obtain copper hydroxide nanoparticles, which specifically includes:
[0018] Light MgO is added to a copper nitrate solution, and the mixture is stirred and reacted at 280-300 K for 7±1 d. The resulting precipitate is filtered, washed and dried to obtain copper hydroxide nanoparticles.
[0019] The concentration of copper nitrate in the copper nitrate solution is 1-1.2 mol / L, and the molar ratio of the light magnesium oxide to the copper nitrate is 1:(2-3).
[0020] Furthermore, the copper hydroxide nanoparticles are dispersed in a cerium nitrate solution, and then a hydrothermal reaction is performed. The obtained precipitate is filtered, washed and dried to obtain a Ce@Cu(OH)2-IE intermediate, which specifically includes:
[0021] The copper hydroxide nanoparticles are dispersed in a cerium nitrate solution, and then a hydrothermal reaction is carried out at 392 to 398 K for 12 to 15 hours. The obtained precipitate is filtered, washed and dried to obtain a Ce@Cu(OH)2-IE intermediate;
[0022] The concentration of cerium nitrate in the cerium nitrate solution is 10±0.5 mmol / L, and the molar ratio of Cu(OH)2 in the copper hydroxide nanoparticles to the cerium nitrate is (30-40):1.
[0023] Furthermore, the Ce@Cu(OH)2-IE intermediate is calcined to obtain a Fenton-like catalytic material CC-IE, which specifically includes:
[0024] The Ce@Cu(OH)2-IE intermediate was calcined in an air atmosphere for 2.5 to 3 hours, the calcination temperature was 773±10K, and the heating rate was 2.5K / min to obtain a Fenton-like catalytic material CC-IE.
[0025] Based on the same inventive concept, the present invention provides a Fenton-like catalytic material for selectively removing phenolic pollutants. The Fenton-like catalytic material is prepared by the above-mentioned method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants.
[0026] Alternatively, the present invention provides a Fenton-like catalytic material for selectively removing phenolic pollutants, wherein the Fenton-like catalytic material is a sheet structure with a thickness of 2 to 8 nm, wherein the main component of the sheet structure is monoclinic CuO with Ce doped in the surface lattice, and in the Fenton-like catalytic material, the molar ratio of cerium element to copper element is 1:(62 to 70).
[0027] Based on the same inventive concept, the present invention provides a Fenton-like catalytic material for selectively removing phenolic pollutants and its application as a persulfate activation catalyst.
[0028] Optionally, the persulfate is permonosulfate (PMS) having the chemical formula H2SO5.
[0029] Based on the same inventive concept, the present invention provides an application of a Fenton-like catalytic material for selectively removing phenolic pollutants in the treatment of wastewater containing phenolic pollutants.
[0030] Based on the same inventive concept, the present invention provides an organic wastewater treatment agent, which comprises permonosulfate and the above-mentioned Fenton-like catalytic material for selectively removing phenolic pollutants, and the mass ratio of the permonosulfate to the Fenton-like catalytic material for selectively removing phenolic pollutants is 1:(0.3~0.4).
[0031] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0032] 1. The present invention discloses a method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants. The method uses light magnesium oxide as a raw material and adopts an ion exchange method to synthesize a Cu(OH)2 precursor, then adopts a hydrothermal ion exchange method to uniformly dope cerium on the surface of Cu(OH)2 to synthesize a Ce@Cu(OH)2-IE intermediate, and finally calcines Ce@Cu(OH)2-IE at a high temperature in air to obtain a Fenton-like catalytic material CC-IE. The catalytic material prepared by the present invention can efficiently activate PMS to generate singlet oxygen, can utilize an oxidative polymerization mechanism to stably remove organic phenolic pollutants in water, and has the advantages of high electron utilization, selective oxidation, non-radical pathway degradation and high TOC removal rate.
[0033] 2. The present invention discloses a Fenton-like catalytic material for selectively removing phenolic pollutants. The Fenton-like catalytic material CC-IE is a sheet structure, the sheet structure is a CuO crystal, the cerium element is uniformly doped in the CuO surface lattice, and the active sites (Cu sites activated by Ce) are uniformly distributed on the surface of the catalytic material. CC-IE has a large number of bridging OH sites due to the strong coordination between Ce and O. - and lattice oxygen on the catalyst, which induces the formation of Cu(III) on the catalyst surface. Cu(III) can not only form an outer layer complex with PMS to promote the generation of superoxide radicals, but also promote the conversion of superoxide radicals into singlet oxygen. Due to its electrophilicity, singlet oxygen preferentially attacks phenolic hydroxyl groups to produce phenoxylium ions. After instantaneous resonance transfer, the positively charged carbon center formed by phenolic hydroxyl groups can be coupled with other negatively charged hydroxyl groups of bisphenol A. This continuous CO coupling reaction enables the continuous growth of the polymer chain, thereby achieving efficient TOC removal performance. In addition, the selective attack of singlet oxygen on phenolic hydroxyl groups in phenolic pollutants enables ultra-high oxidant electron utilization.
[0034] 3. The present invention discloses a Fenton-like catalytic material for selectively removing phenol pollutants. The high-valent metal on the surface of the Fenton-like catalytic material CC-IE induces the generation of singlet oxygen, promotes the oxidation reaction of the non-free radical pathway, has a stronger anti-interference ability for wastewater with a complex water background, and the special chemical environment on the surface of CC-IE induces the occurrence of oxidative polymerization reaction, thereby realizing the recovery of organic carbon in the water body. CC-IE can efficiently activate PMS to generate singlet oxygen, and utilizes the oxidative polymerization mechanism to stably remove organic phenol pollutants in water. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 XPS spectra of Cu 2p orbitals in the catalytic material CC-IE of the present invention and ordinary CuO.
[0037] Figure 2 The figure shows the removal effect of the catalytic material CC-IE of the present invention on the difficult-to-degrade pollutant BPA under different salt ion backgrounds.
[0038] Figure 3 The figure shows the removal effect of the catalytic material CC-IE of the present invention on the difficult-to-degrade pollutant BPA under different pH conditions.
[0039] Figure 4 This is the Raman spectrum of the catalytic material CC-IE of the present invention.
[0040] Figure 5 Singlet oxygen EPR capture characterization spectrum was performed for the catalytic material CC-IE of the present invention.
[0041] Figure 6 This is an image of the TOC removal rate of different pollutants by the catalytic material CC-IE of the present invention.
[0042] Figure 7 This is a TEM image of the catalytic material of the present invention after the CC-IE reaction is completed. DETAILED DESCRIPTION
[0043] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0044] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0045] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0046] The technical principle of the present invention is as follows:
[0047] The present invention aims at the problems of low utilization efficiency of oxidant of current persulfate activated catalyst, low TOC removal efficiency, and large CO2 emission that is difficult to avoid, and develops a Fenton-like persulfate activated catalytic material CC-IE with high electron utilization, selective oxidation characteristics, non-radical degradation and high TOC removal rate. CC-IE is a sheet structure, and active sites are evenly distributed on the surface of the catalytic material. Cerium is evenly doped in the CuO surface lattice, which can efficiently activate PMS to generate singlet oxygen, and utilizes the oxidative polymerization mechanism to stably remove and recover organic carbon materials in phenol wastewater.
[0048] The present invention provides a method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants, the preparation method comprising:
[0049] S1. adding light MgO to a copper nitrate solution, stirring the reaction for a certain period of time, filtering, washing and drying the resulting precipitate to obtain copper hydroxide nanoparticles;
[0050] S2. dispersing the copper hydroxide nanoparticles in a cerium nitrate solution, and then performing a hydrothermal reaction. The resulting precipitate is filtered, washed and dried to obtain a Ce@Cu(OH)2-IE intermediate;
[0051] S3. calcining the Ce@Cu(OH)2-IE intermediate to obtain a Fenton-like catalytic material CC-IE.
[0052] Step S1 specifically includes:
[0053] Light MgO is added to a copper nitrate solution, and the mixture is stirred and reacted at 280-300 K for 7±1 d. The resulting precipitate is filtered, washed and dried to obtain copper hydroxide nanoparticles.
[0054] The concentration of copper nitrate in the copper nitrate solution is 1-1.2 mol / L, and the molar ratio of the light magnesium oxide to the copper nitrate is 1:(2-3).
[0055] In the present invention, light magnesium oxide has smaller particle size and larger specific surface area, so the prepared material can provide a higher active site density, while heavy magnesium oxide does not have this advantage.
[0056] In the present invention, light MgO is added to a copper nitrate solution, and the reaction is stirred at 280-300K for 7±1d, which can ensure full utilization of the MgO raw material. A reaction time of less than 6d will lead to insufficient reaction, and ultimately the yield and activity of the effective catalytic material will be reduced. A reaction time of more than 8d will not significantly improve the yield and catalytic activity.
[0057] Step S2 specifically includes:
[0058] The copper hydroxide nanoparticles are dispersed in a cerium nitrate solution, and then a hydrothermal reaction is carried out at 392 to 398 K for 12 to 15 hours. The obtained precipitate is filtered, washed and dried to obtain a Ce@Cu(OH)2-IE intermediate;
[0059] The concentration of cerium nitrate in the cerium nitrate solution is 10±0.5 mmol / L, and the molar ratio of Cu(OH)2 in the copper hydroxide nanoparticles to the cerium nitrate is (30-40):1.
[0060] In the present invention, the hydrothermal reaction temperature is 392-398K, which can ensure the full progress of the reaction and proper ion exchange at the solid-liquid interface. Temperatures below this range will result in slow reaction, while temperatures above this range will increase the Ce density on the surface of the final material and reduce its activity.
[0061] In the present invention, the concentration of cerium nitrate in the cerium nitrate solution is 10±0.5 mmol / L, which ensures a reasonable distribution of Ce elements on the surface of the final catalytic material. A higher concentration will cause aggregation of Ce oxide particles on the surface of the final synthesized catalytic material, and a lower concentration cannot form sufficient Ce site density on the material surface, thereby reducing activity.
[0062] The molar ratio of Cu(OH)2 in the copper hydroxide nanoparticles to the cerium nitrate is (30-40):1, which can ensure a reasonable copper-cerium element ratio in the catalytic material. A higher copper-cerium element ratio will result in an inability to form sufficient Ce site density on the material surface, thereby reducing activity. A lower copper-cerium element ratio will cause cerium particles to aggregate and cover the active copper sites.
[0063] Step S3 specifically includes:
[0064] The Ce@Cu(OH)2-IE intermediate was calcined in an air atmosphere for 2.5 to 3 hours, the calcination temperature was 773±10K, and the heating rate was 2.5K / min to obtain a Fenton-like catalytic material CC-IE.
[0065] In the present invention, the Ce@Cu(OH)2-IE intermediate is calcined at 773±10K for 2.5 to 3h to fully oxidize the intermediate into an oxide to ensure that an effective lattice structure can be formed. A low calcination temperature or insufficient calcination time will result in an incomplete lattice on the oxide surface, which is not conducive to the electron transfer of the catalytic reaction. A too long calcination time or a high temperature will result in more energy consumption and increase the catalyst synthesis cost.
[0066] Specifically, a method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants comprises:
[0067] S1. A certain amount of light MgO was added to a copper nitrate solution at 280-300K under constant magnetic stirring, and the reaction lasted for 7±1d. The obtained precipitate was filtered and washed with deionized water six times, and then dried in an oven for 6 hours to obtain copper hydroxide nanoparticles;
[0068] The concentration of copper nitrate in the copper nitrate solution is 1-1.2 mol / L, and the molar ratio of the light magnesium oxide to the copper nitrate is 1:(2-3).
[0069] S2. A quantitative amount of the copper hydroxide nanoparticles is dispersed in a cerium nitrate solution, and then the dispersion is transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, and a hydrothermal reaction is carried out at 392 to 398 K for 12 to 15 hours. After the reaction, the precipitate is filtered and washed with deionized water for 6 times, and then dried in an oven to obtain a Ce@Cu(OH)2-IE intermediate;
[0070] The concentration of cerium nitrate in the cerium nitrate solution is 10±0.5 mmol / L, and the molar ratio of the copper hydroxide nanoparticles to the cerium nitrate is (30-40):1.
[0071] S3. The Ce@Cu(OH)2-IE intermediate is transferred into a ceramic crucible and placed in a tubular furnace. It is calcined for 2.5 to 3 h in an air atmosphere at a calcination temperature of 773±10 K and a heating rate of 2.5 K / min to obtain a Fenton-like catalytic material CC-IE.
[0072] The following is a detailed description of a method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants in the present application in combination with examples and experimental data.
[0073] Example 1
[0074] This embodiment provides a method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants, which specifically includes:
[0075] (1) A certain amount of light MgO was added to a copper nitrate solution at 293 K under constant magnetic stirring and reacted for 7 days. The obtained precipitate was filtered and washed with deionized water six times, and then dried in an oven for 6 hours to obtain copper hydroxide nanoparticles;
[0076] The concentration of copper nitrate in the copper nitrate solution is 1.1 mol / L, and the molar ratio of the light magnesium oxide to the copper nitrate is 2:5.
[0077] (2) dispersing a certain amount of the copper hydroxide nanoparticles in a cerium nitrate solution, and then transferring the dispersion into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, performing a hydrothermal reaction at 393 K for 12 h, filtering the precipitate after the reaction and washing it with deionized water for 6 times, and then drying it in an oven to obtain a Ce@Cu(OH)2-IE intermediate;
[0078] The concentration of cerium nitrate in the cerium nitrate solution is 10 mmol / L, and the molar ratio of the copper hydroxide nanoparticles to the cerium nitrate is 35:1.
[0079] (3) The Ce@Cu(OH)2-IE intermediate was transferred into a ceramic crucible and placed in a tubular furnace, and calcined for 3 h in an air atmosphere at a calcination temperature of 773 K and a heating rate of 2.5 K / min to obtain a Fenton-like catalytic material CC-IE.
[0080] The above materials were characterized by XPS, and the results are as follows Figure 1 It can be found that after Ce is doped on the CuO surface lattice, the binding energy of Cu2p moves from 933.4eV to 933.9eV, which indicates that the Cu element in CC-IE has a higher valence state than the copper element in copper oxide, indicating that there is high-valent metallic copper on the CC-IE surface.
[0081] Example 2
[0082] This example conducts a pollutant degradation experiment using the Fenton-like catalytic material CC-IE prepared in Example 1.
[0083] Pollutant degradation experiments were all carried out in 250 mL conical flasks. 100 mL of different anions (Cl - , NO3 - , HCO3 - ,CO3 2- , SO4 2- ) bisphenol A solution (20 mg / L) with an anion concentration of 5 mmol / L, 0.1 g of the catalyst prepared according to Example 1 was added, ultrasonically dispersed for 20 min to form a uniform suspension, and then stirred for 10 min to establish adsorption-desorption equilibrium. 0.35 g of PMS was added to the suspension to initiate the reaction. 0.5 mL of the suspension was taken out at fixed time intervals and injected with 1.0 mL of methanol for chemical quenching, and then the residual bisphenol A concentration was measured.
[0084] BPA (bisphenol A) removal rate curve is as follows Figure 2 As shown, Figure 2 The control group was a bisphenol A solution (20 mg / L) without the addition of anions. Figure 2This indicates that CC-IE can also achieve excellent degradation effects in water matrices under different salt ion backgrounds.
[0085] Example 3
[0086] This example tests the removal efficiency of BPA by CC-IE prepared in Example 1 under different pH conditions.
[0087] 100 mL of bisphenol A solution (20 mg / L) was added to each conical flask, the pH value was adjusted (3, 5, 7, 9, 10), and 0.1 g of the catalyst CC-IE prepared in Example 1 was added. After ultrasonic dispersion for 20 min, a uniform suspension was formed, and then stirred for 10 min to establish adsorption-desorption equilibrium. 0.035 g of PMS was added to the suspension to initiate the reaction. 0.5 mL of the suspension was taken out at fixed time intervals and 1.0 mL of methanol was injected for chemical quenching, and then the residual bisphenol A concentration was measured.
[0088] BPA removal rate curve is as follows Figure 3 shown. Figure 3 This indicates that CC-IE can also achieve excellent degradation effects in water matrices under different pH conditions.
[0089] Example 4
[0090] In this example, the CC-IE prepared in Example 1 was subjected to Raman spectroscopy analysis and EPR capture characterization.
[0091] 1. Raman spectroscopy analysis was performed on the CC-IE prepared in Example 1. The results are as follows: Figure 4 As shown, Figure 4 The ions attributed to CeO2 (at 460 cm -1 at 285 cm -1 , 337cm -1 ) Raman active vibration modes. Compared with pure CuO and CeO2, the peaks in CC-IE become broader and show an obvious shift to low frequencies, which indicates that the strong lattice distortion and residual stress in the lattice structure induce the formation of a large number of lattice defects, resulting in more active sites.
[0092] 2. The CC-IE prepared in Example 1 was subjected to EPR capture characterization, and the results were as follows: Figure 5 As shown by Figure 5 It can be seen that the main active substance produced in the reaction is singlet oxygen, indicating that the reaction pathway mediated by CC-IE is a non-radical reaction pathway dominated by singlet oxygen.
[0093] Example 5
[0094] This example tests the TOC removal rate of the catalytic material CC-IE for different pollutants.
[0095] 100 mL of bisphenol A (BPA), phenol (PhOH), 2,6-dimethylphenol (2,6-M-PhOH), and 4-chlorophenol (4-CP) solution (20 mg / L) were added to a conical flask, and then 0.1 g of the catalyst CC-IE prepared according to Example 1 was added. After ultrasonic dispersion for 20 min, a uniform suspension was formed, and then stirred for 10 min to establish adsorption-desorption equilibrium. 0.035 g of PMS was added to the suspension to initiate the reaction. 0.5 mL of the suspension was taken out at fixed time intervals and 1.0 mL of methanol was injected for chemical quenching, and then the remaining TOC in the solution was measured.
[0096] TOC removal rate curve is as follows Figure 6 shown. Figure 6 This indicates that CC-IE can achieve excellent TOC removal effects on various phenolic pollutants in a short period of time.
[0097] Example 6
[0098] This example observes the TEM image after the CC-IE catalytic reaction is completed.
[0099] 100 mL of bisphenol A solution (20 mg / L) was added to each conical flask, and then 0.1 g of the catalyst prepared according to Example 1 was added. After ultrasonic dispersion for 20 min, a uniform suspension was formed, and then stirred for 10 min to establish adsorption-desorption equilibrium. 0.035 g of PMS was added to the suspension to initiate the reaction. After reacting for 30 min, the suspension was filtered and the obtained residue was dried. TEM images were taken, as shown in FIG. Figure 7 shown. Figure 7 Amorphous polymeric substances can be observed on the surface of the material, indicating that the organic carbon in the system is removed by a polymerization mechanism.
[0100] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0101] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0102] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants, characterized in that: The preparation method comprises: Light MgO is added to a copper nitrate solution, stirred and reacted for a certain period of time, and the resulting precipitate is filtered, washed and dried to obtain copper hydroxide nanoparticles; The copper hydroxide nanoparticles are dispersed in a cerium nitrate solution, followed by a hydrothermal reaction, and the resulting precipitate is filtered, washed, and dried to obtain a Ce@Cu(OH)2-IE intermediate; The Ce@Cu(OH)2-IE intermediate is calcined to obtain a Fenton-like catalytic material CC-IE.
2. The method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants according to claim 1, characterized in that: The method comprises adding light MgO to a copper nitrate solution, stirring and reacting for a certain period of time, filtering, washing and drying the obtained precipitate to obtain copper hydroxide nanoparticles, and specifically comprising: Light MgO is added to a copper nitrate solution, and the mixture is stirred and reacted at 280-300 K for 7±1 d. The resulting precipitate is filtered, washed and dried to obtain copper hydroxide nanoparticles. The concentration of copper nitrate in the copper nitrate solution is 1-1.2 mol / L, and the molar ratio of the light magnesium oxide to the copper nitrate is 1:(2-3).
3. The method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants according to claim 1, characterized in that: The copper hydroxide nanoparticles are dispersed in a cerium nitrate solution, and then a hydrothermal reaction is performed. The obtained precipitate is filtered, washed and dried to obtain a Ce@Cu(OH)2-IE intermediate, which specifically includes: The copper hydroxide nanoparticles are dispersed in a cerium nitrate solution, and then a hydrothermal reaction is carried out at 392 to 398 K for 12 to 15 hours. The obtained precipitate is filtered, washed and dried to obtain a Ce@Cu(OH)2-IE intermediate; The concentration of cerium nitrate in the cerium nitrate solution is 10±0.5 mmol / L, and the molar ratio of Cu(OH)2 in the copper hydroxide nanoparticles to the cerium nitrate is (30-40):
1.
4. The method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants according to claim 1, characterized in that: The calcining of the Ce@Cu(OH)2-IE intermediate to obtain the Fenton-like catalytic material CC-IE specifically comprises: The Ce@Cu(OH)2-IE intermediate is calcined in an air atmosphere for 2.5 to 3 hours, the calcination temperature is 773±10K, and the heating rate is 2.5K / min to obtain a Fenton-like catalytic material CC-IE.
5. A Fenton-like catalytic material for selectively removing phenolic pollutants, characterized in that: The Fenton-like catalytic material is prepared by the method for preparing a Fenton-like catalytic material for selectively removing phenolic pollutants according to any one of claims 1 to 4.
6. A Fenton-like catalytic material for selectively removing phenolic pollutants, characterized in that: The Fenton-like catalytic material is a sheet structure with a thickness of 2 to 8 nm. The main component of the sheet structure is monoclinic CuO with Ce doped in the surface lattice. In the Fenton-like catalytic material, the molar ratio of cerium element to copper element is 1:(62 to 70).
7. Use of a Fenton-like catalytic material for selectively removing phenolic pollutants as claimed in claim 5 or 6 as a persulfate activation catalyst.
8. The use according to claim 7, characterized in that: The persulfate is peroxymonosulfate, and its chemical formula is H2SO5.
9. Use of a Fenton-like catalytic material for selectively removing phenolic pollutants as claimed in claim 5 or 6 in the treatment of wastewater containing phenolic pollutants.
10. An organic wastewater treatment agent, characterized in that: The organic wastewater treatment agent comprises peroxymonosulfate and a Fenton-like catalytic material for selectively removing phenolic pollutants as described in claim 5 or 6, and the mass ratio of the peroxymonosulfate to the Fenton-like catalytic material for selectively removing phenolic pollutants is 1:(0.3-0.4).
Citation Information
Patent Citations
Cluster manganese dioxide loaded iron Fenton-like catalyst and preparation method thereof
CN113426455A
A method for preparing a highly efficient catalyst for the removal of ciprofloxacin using a Fenton-like process.
CN114870845B
Method for driving Fenton-like reaction system by activating FeIII through PDA-coated MoN and application of method
CN117299180A
Cited By
Method for degrading antibiotic wastewater based on SR-AOPs mediated Fenton system
CN120172532A
Method and device for activating monopersulfate to efficiently degrade phenol-containing wastewater and synergistically remove other pollutants and application
CN122187225A
A method, device and application for activating monopersulfate to efficiently degrade phenol-containing wastewater and achieve synergistic removal of other pollutants
CN122187225B